Securing Communication in Internet of Vehicles using Collaborative Cryptography and Intelligent Reflecting Surfaces - Ahmed, Aljumaili; Trabelsi, Hafedh; Jerbi, Wassim; Hazim, Rafal (Journal of Robotics and Control (JRC), 2024)
The Internet of Vehicles (IoV) is revolutionizing transportation systems by enabling seamless communication and collaboration among vehicles, roadside units (RSUs), and cloud servers. However, the dynamic and diverse nature of IoV environments raises significant concerns regarding security vulnerabilities and operational efficiency. In response to these challenges, this study proposes an innovative approach that integrates collaborative cryptographic techniques with intelligent reflecting surfaces (IRS). Our approach leverages advanced encryption methods, such as the Advanced Encryption Standard (AES), to ensure secure data transmission, while intelligent reflecting surfaces dynamically adjust their reflective properties to enhance signal propagation and reception. We present a comprehensive network model and algorithmic framework for implementing our proposed strategy, with a specific emphasis on cryptographic protocols and the role of intelligent reflecting surfaces in enhancing both communication security and efficiency. Through theoretical analysis and discussion, we highlight the potential advantages of integrating intelligent reflecting surfaces into secure physical layer (PL), IoV networks, including expanded network coverage, reduced communication overhead, and enhanced energy efficiency. Moreover, we address security threats and vulnerabilities in IoV environments, including potential attacks such as eavesdropping, data tampering, and denial of service. We discuss strategies for mitigating these security risks through the combined use of cryptographic techniques and intelligent reflecting surfaces, thereby bolstering the resilience and robustness of IoV systems.